A hard carbon negative electrode material derived from Cyclobalanopsis glauca and a preparation method thereof

Through microwave-assisted alkali melt-acid leach technology and microwave carbonization technology, the problems of high impurity content and high production energy consumption of biomass hard carbon materials in traditional methods are solved, and the preparation of hard carbon materials with high purity and high closed porosity are achieved. Suitable for low-cost sodium ion battery field.

CN118637600BActive Publication Date: 2025-02-11YANGTZE DELTA REGION INST OF UNIV OF ELECTRONICS SCI & TECH OF CHINE (HUZHOU)
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411124915.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2025-02-11
Estimated Expiration
2044-08-16

AI Technical Summary

Technical Problem

The traditional lithium-ion battery negative electrode material graphite cannot be used in sodium ion batteries, and the biomass hard carbon negative electrode material has problems such as high impurity content, high production energy consumption and high cost, making it difficult to achieve high purity and low cost hard carbon material preparation.

Method used

Microwave-assisted alkali melt-acid leaching technology is used to quickly and efficiently remove impurities in the precursor of Qinggang wood, and combine microwave carbonization technology to achieve the preparation of hard carbon materials with high purity and high closed porosity.

Benefits of technology

The rapid preparation of high-purity and high-closed porosity hard carbon materials is achieved, reducing production energy consumption and cost, and improving the specific capacity and cycle stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118637600B_ABST
    Figure CN118637600B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a hard carbon negative electrode material derived from cycad glauca, comprising the following steps: (1) washing and drying the cycad glauca, crushing it into wood powder using a crusher, and then pre-carbonizing it; (2) mixing the carbon powder after the pre-carbonization with alkali powder by ball milling, and then putting it into a microwave reactor for microwave-assisted alkali melting to obtain a product; (3) then acid leaching the product, and then washing and drying it to obtain the impurity-removed carbon powder; (4) putting the impurity-removed carbon powder into a microwave reactor for microwave high-temperature carbonization, and then ball milling and screening to obtain the hard carbon negative electrode material derived from cycad glauca. The hard carbon negative electrode material prepared by the invention has the advantages of high capacity, long cycle, and low cost, and the cycad glauca resource is abundant and renewable, and has good market application prospects in the field of low-cost sodium ion batteries such as energy storage and two-wheel electric vehicles in the future.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of negative electrode material preparation, and in particular to a hard carbon negative electrode material derived from Cyclobalanopsis glauca and a preparation method thereof. Background Art

[0002] Lithium-ion batteries are currently widely used in electronic devices and electric vehicles. However, the scarcity and uneven geographical distribution of lithium resources limit their application in large-scale energy storage. Sodium-ion batteries are a promising alternative to lithium-ion batteries due to their low cost and widespread sodium resource reserves. However, the traditional lithium battery negative electrode material graphite cannot be used in sodium-ion batteries due to its small interlayer spacing. Researchers have developed a series of hard carbon negative electrode materials based on carbon-containing raw materials such as biomass, asphalt, anthracite, and resin.

[0003] Among them, biomass materials have become high-quality precursor materials for negative electrode materials of sodium ion batteries due to their abundant reserves, low cost, renewable advantages and relatively simple and mature processing technology. At present, the more common biomass materials are coconut shells, bamboo, straw, wood, etc., but this precursor also has problems such as high impurity content, batch instability, high production cost, and difficult to control pore structure. The general impurity removal method is mainly through alkali washing and acid washing. For example, the patent CN202310379981 mentioned that "take wood chips, add them to acid or alkali solution for ultrasonic treatment, the ultrasonic treatment time is 0.5-1.5h, and the weight ratio of wood chips to acid or alkali solution is 1:4-1:6". Ordinary acid washing and alkali washing are often difficult to completely remove impurities and will produce a large amount of wastewater. The traditional electric furnace heating mode also produces high energy consumption and a long production cycle in the hard carbon production process. For example, Patent 201810475103.1 mentioned that "in an inert atmosphere or in the absence of oxygen, hardwood is treated according to the following temperature change conditions; (a) heating from room temperature to 210-250°C at a heating rate of 0.05-2°C / min; (b) heating from 210-250°C to 760-850°C at a heating rate of 0.1-3°C / min; (c) heating from 760-850°C to 1100-1450°C at a heating rate of 0.5-4°C / min, and keeping warm for 0.5-6.0h; (d) cooling from 1100-1450°C to room temperature at a cooling rate of 0.5-20°C / min". Therefore, the development of new high-purity, high-performance, and low-cost hard carbon negative electrode materials is an urgent problem to be solved in the development of sodium-ion batteries.

[0004] Qingao wood is a hardwood with a high lignin content and a high carbon yield during carbonization. It is widely distributed in the southwest region and is a high-quality hard carbon precursor material. However, it is difficult to completely remove impurity elements such as silicon, aluminum, and calcium in wood, and the carbonization process is energy-intensive and costly. The price of the hard carbon material obtained remains high, limiting its application in low-cost sodium ion batteries such as energy storage. The traditional heating method is to gradually heat the material through an external heat source, and the heating speed is often not too fast, resulting in a long production cycle and high energy consumption. Invention patent 201310025196.5 discloses a production process for binchotan, mentioning that "the carbon production process of the present invention uses specially selected deep mountain ebony wood and Qingao wood as raw materials, which are carbonized at low temperature for a long time (about 30 days) and smelted at high temperature above 1000 degrees." However, microwave heating is a volume heating caused by the dielectric loss of the material itself in the electromagnetic field, so molecular level stirring can be achieved, heating is faster and more uniform, and energy consumption is lower. Microwave-assisted alkali melting technology can ensure the efficient removal of impurity elements such as silicon and aluminum in the system under the action of high-temperature molten alkali. Microwave carbonization technology can greatly reduce production energy consumption and production time, while increasing the closed-cell structure in the system. Summary of the invention

[0005] The present invention provides a hard carbon negative electrode material derived from Cyclobalanopsis glauca and a preparation method thereof. The microwave-assisted alkali melting-acid leaching technology is adopted to quickly and efficiently remove impurity elements such as silicon and aluminum in the Cyclobalanopsis glauca precursor, thereby improving the disorder and purity of the carbon structure, while reducing energy consumption and production time. Combined with the subsequent microwave carbonization technology, the efficient and rapid preparation of high-purity biomass hard carbon materials is achieved, while greatly reducing energy consumption and production costs, so as to overcome the problems of high impurity content and high production energy consumption of biomass hard carbon materials.

[0006] In order to achieve the above technical objectives, the present invention adopts the following technical solutions.

[0007] A method for preparing a hard carbon negative electrode material derived from Cyclobalanopsis glauca comprises the following steps.

[0008] (1) The cycad wood is cleaned, dried, crushed into wood powder using a crusher, and then pre-carbonized.

[0009] (2) The carbon powder after pre-carbonization treatment is mixed with alkali powder by ball milling, and then placed in a microwave reactor for microwave-assisted alkali melting treatment to obtain a product and remove silicon, aluminum and other elements in the system.

[0010] (3) The product is then subjected to acid leaching to remove excess alkali and impurity elements such as calcium, iron, sodium, and potassium in the system, and then washed and dried to obtain impurity-free carbon powder.

[0011] (4) The carbon powder after impurities removal is placed in a microwave reactor for microwave high-temperature carbonization treatment, and then ball milled and sieved to prepare a hard carbon negative electrode material derived from Cyclobalanopsis glauca.

[0012] Preferably, in step (1), Cyclobalanopsis glauca is selected as the raw material, which is washed with clean water, dried, and then crushed into wood powder using a crusher. The average particle size of the wood powder is 0.2-10 mm. The smaller size and increased specific surface area are conducive to the subsequent dissolution of impurities by alkali and acid.

[0013] Preferably, in step (1), the wood powder enters a tubular furnace for pre-carbonization at a temperature of 400-800°C, a heating time of 1-24h, a heating rate of 2-10°C / min, and the pre-carbonization atmosphere is an argon or nitrogen inert atmosphere.

[0014] Preferably, the alkali powder in step (2) is selected from one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, calcium oxide, and calcium carbonate, the mass ratio of carbon powder to alkali powder is 100:1-5:1, the ball milling speed is 200-600rpm, and the ball milling time is 1-6h. The use of alkali powder can remove impurity elements such as silicon and aluminum in the system in a targeted manner, and at the same time slightly etch the carbon skeleton to increase the micropore content.

[0015] Preferably, in step (2), the microwave heating temperature is 300-800°C, the heating time is 0.1-5h, the heating rate is 50-500°C / min, and the microwave heating atmosphere is an argon or nitrogen inert atmosphere. Microwave heating can achieve rapid temperature rise and fall, which is more energy-efficient than traditional electric furnace heating and also shortens the production cycle.

[0016] Preferably, the material after microwave-assisted alkali melting treatment in step (3) is pickled, and the acid is selected from one or more of hydrochloric acid, sulfuric acid, nitric acid, oxalic acid, phosphoric acid, citric acid, and acetic acid, the acid concentration is 0.2-5 mol / L, the pickling temperature is 20-100° C., and the pickling time is 2-12 hours. The purpose of pickling is to remove excess alkali and metal impurity elements such as sodium, potassium, calcium, and iron in the precursor.

[0017] Preferably, in step (3), clean water is used for washing until neutrality, and vacuum heating and drying are performed at a temperature of 60-150° C. for 12-48 hours.

[0018] Preferably, the carbon powder after impurities removal in step (4) is placed in a microwave reaction sintering furnace for high-temperature carbonization treatment, the microwave heating temperature is 1000-1600°C, the heating time is 0.1-10h, the heating rate is 100-1200°C / min, and the microwave heating atmosphere is an argon or nitrogen inert atmosphere.

[0019] Preferably, in step (4), the ball milling speed is 200-600 rpm, and the ball milling time is 1-12 h; and then the product is sieved with a mesh size of 200-500 mesh.

[0020] The present invention also provides a hard carbon negative electrode material derived from Cyclobalanopsis glauca, wherein the impurity content of the hard carbon negative electrode material is 0-0.5%, and the specific surface area is 1-10m 2 / g, compacted density 1.2-2.0g / cm 3 .

[0021] Compared with the prior art, the present invention has the following innovations and advantages.

[0022] (1) The present invention proposes for the first time a microwave-assisted alkali fusion-acid leaching method for rapid and efficient impurity removal of biomass materials, which is used to prepare high-purity and high-closed-pore Quercus glauca-based hard carbon materials, and is applied in the field of low-cost sodium-ion batteries. The currently reported biomass hard carbon preparation processes are still limited to the traditional electric furnace heating carbonization method, and the removal of impurities mostly adopts the acid washing and alkali washing methods, which not only have high energy consumption, long cycle, and high pollution, but also make it difficult to achieve the preparation of high-purity hard carbon. The microwave-assisted alkali fusion-acid leaching method and microwave carbonization method proposed in the present invention can greatly reduce energy consumption, shorten the preparation cycle, and reduce production costs. Rapid thermal shock is also conducive to the formation of closed-pore structure, improving the specific capacity of hard carbon negative electrodes, and filling the technical gap of low-cost and high-purity biomass hard carbon negative electrodes.

[0023] (2) The present invention can be used to prepare a hard carbon material derived from Cyclobalanopsis glauca, which is used as a negative electrode material for sodium ion batteries. The microwave-assisted alkaline melting-acid leaching method can achieve rapid and efficient impurity removal of biomass precursors, and microwave carbonization technology can significantly reduce production energy consumption and costs, thereby achieving the preparation of high-purity and high-closed-porosity hard carbon materials. The hard carbon negative electrode material prepared by the present invention has the advantages of high capacity, long cycle, and low cost, and Cyclobalanopsis glauca resources are abundant and renewable. In the future, it has good market application prospects in the fields of low-cost sodium ion batteries such as energy storage and two-wheeled electric vehicles. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the SEM image of the material prepared in Example 1.

[0025] Figure 2 This is the charge and discharge performance diagram of the material prepared in Example 1. DETAILED DESCRIPTION

[0026] The present invention is further described below in conjunction with specific embodiments, which should be understood as being only used to illustrate the present invention and not to limit the scope of protection of the present invention. After reading the contents of the present invention, various changes or modifications made to the present invention based on the principles of the present invention also fall within the scope defined by the claims of the present invention.

[0027] In an embodiment of the present invention, a method for preparing a hard carbon negative electrode material derived from Cyclobalanopsis glauca comprises the following steps.

[0028] (1) The cycad wood is cleaned, dried, crushed into wood powder using a crusher, and then pre-carbonized.

[0029] (2) The carbon powder after pre-carbonization treatment is mixed with alkali powder by ball milling, and then placed in a microwave reactor for microwave-assisted alkali melting treatment to obtain a product and remove silicon, aluminum and other elements in the system.

[0030] (3) The product is then subjected to acid leaching to remove excess alkali and impurity elements such as calcium, iron, sodium, and potassium in the system, and then washed and dried to obtain impurity-free carbon powder.

[0031] (4) The carbon powder after impurities removal is placed in a microwave reactor for microwave high-temperature carbonization treatment, and then ball milled and sieved to prepare a hard carbon negative electrode material derived from Cyclobalanopsis glauca.

[0032] In order to make the disclosure of the present invention more complete, it is described below through more specific embodiments.

[0033] Example 1.

[0034] The cycad wood was crushed into wood powder and pre-carbonized in a tubular furnace with a heating temperature of 600°C, a heating time of 5h, and a heating rate of 5°C / min. The pre-carbonized carbon powder was ball-milled with potassium hydroxide powder. The mass ratio of carbon powder to potassium hydroxide was 20:1, the ball milling speed was 300rpm, and the ball milling time was 1h. The blended material was placed in a microwave reaction sintering furnace with a microwave heating temperature of 600°C, a heating time of 1h, and a heating rate of 60°C / min. Then, 1mol / L sulfuric acid was used for pickling at a pickling temperature of 80°C and a pickling time of 6h. Then, the material was washed with clean water until neutral, and dried by vacuum heating at 100°C. The material was then placed in a microwave reaction sintering furnace and microwave heated at 1400°C for 2h with a heating rate of 300°C / min. The material after high-temperature carbonization was ball-milled with a ball milling speed of 500rpm and a ball milling time of 3h. After screening through a 300-mesh sieve, a hard carbon negative electrode material was obtained, such as Figure 1 As shown, the average particle size of the obtained material is about 3μm and the specific surface area is 4.1m 2 / g, impurity content is less than 0.2%, assembled sodium ion half-battery test initial capacity is 372mAh / g, such as Figure 2 As shown, the platform capacity below 0.1V reaches more than 220mAh / g, which means that there are a large number of closed-pore structures in the hard carbon material system for sodium storage, thereby obtaining a higher specific capacity.

[0035] Example 2.

[0036] The cycad wood was crushed into wood powder and pre-carbonized in a tubular furnace with a heating temperature of 500℃, a heating time of 2h, and a heating rate of 5℃ / min. The pre-carbonized carbon powder was ball-milled with potassium hydroxide powder, with a mass ratio of carbon powder to potassium hydroxide of 10:1, a ball milling speed of 300rpm, and a ball milling time of 1h. The blended material was placed in a microwave reaction sintering furnace, with a microwave heating temperature of 700℃, a heating time of 1h, and a heating rate of 70℃ / min. Then, 1mol / L hydrochloric acid was used for pickling, with a pickling temperature of 50℃ and a pickling time of 10h. Then, the material was washed with clean water until neutral, and dried by vacuum heating at 100℃. The material was then placed in a microwave reaction sintering furnace, microwave heated at 1500℃ for 2h, and a heating rate of 300℃ / min. The material after high-temperature carbonization was ball milled, with a ball milling speed of 500rpm and a ball milling time of 2h. After sieving through a 250-mesh sieve, the hard carbon negative electrode material was obtained. The sodium ion half-battery was assembled and tested with an initial capacity of 370 mAh / g and a specific surface area of ​​3.9 m 2 / g.

[0037] Although the present invention has been illustrated and described with respect to the preferred embodiments, it will be appreciated by those skilled in the art that various changes and modifications may be made to the present invention without departing from the scope of the present invention as defined by the claims.

Claims

1. A method for preparing a hard carbon negative electrode material derived from Cyclobalanopsis glauca, characterized in that: The following steps are involved: (1) The Cyclobalanopsis glauca wood is cleaned, dried, crushed into wood powder using a crusher, and then pre-carbonized; (2) The carbon powder after pre-carbonization treatment is mixed with alkali powder by ball milling, and then placed in a microwave reactor for microwave-assisted alkali melting treatment to obtain a product; (3) The product is then subjected to acid leaching treatment, and then washed and dried to obtain impurity-free carbon powder; (4) placing the impurity-removed carbon powder into a microwave reactor for microwave high-temperature carbonization treatment, and then subjecting the carbon powder to ball milling and screening to prepare a hard carbon negative electrode material derived from Cyclobalanopsis glauca; In step (1), the wood powder enters a tubular furnace for pre-carbonization at a temperature of 400-800°C, a heating time of 1-24h, a heating rate of 2-10°C / min, and a pre-carbonization atmosphere of argon or nitrogen inert atmosphere; The alkali powder described in step (2) is selected from one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, calcium oxide, and calcium carbonate, the mass ratio of carbon powder to alkali powder is 100:1-5:1, the ball milling speed is 200-600rpm, and the ball milling time is 1-6h; Step (2) in which the microwave heating temperature is 300-800 ℃, the heating time is 0.1-5h, the heating rate is 50-500 ℃ / min, and the microwave heating atmosphere is an inert atmosphere of argon or nitrogen; The carbon powder after impurities removal in step (4) is placed in a microwave reaction sintering furnace for high-temperature carbonization treatment, the microwave heating temperature is 1000-1600°C, the heating time is 0.1-10h, the heating rate is 100-1200°C / min, and the microwave heating atmosphere is an argon or nitrogen inert atmosphere.

2. The method for preparing the hard carbon negative electrode material derived from Cyclobalanopsis glauca according to claim 1, characterized in that: The average particle size of the wood powder in step (1) is 0.2-10 mm.

3. The method for preparing the hard carbon negative electrode material derived from Cyclobalanopsis glauca according to claim 1, characterized in that: In step (3), the material after microwave-assisted alkali melting treatment is pickled, the acid is selected from one or more of hydrochloric acid, sulfuric acid, nitric acid, oxalic acid, phosphoric acid, citric acid, and acetic acid, the acid concentration is 0.2-5 mol / L, the pickling temperature is 20-100° C., and the pickling time is 2-12 h.

4. The method for preparing the hard carbon negative electrode material derived from Cyclobalanopsis glauca according to claim 1, characterized in that: In step (3), the product is washed with clean water until it becomes neutral, and then dried by vacuum heating at a temperature of 60-150° C. for 12-48 hours.

5. The method for preparing the hard carbon negative electrode material derived from Cyclobalanopsis glauca according to claim 1, characterized in that: In step (4), the ball milling speed is 200-600 rpm, and the ball milling time is 1-12 hours; and then the product is sieved, with a mesh size of 200-500 meshes.

6. A hard carbon negative electrode material derived from Cyclobalanopsis glauca prepared according to the method according to any one of claims 1 to 5, characterized in that: The impurity content of the hard carbon negative electrode material is 0-0.5%, and the specific surface area is 1-10m 2 / g, compacted density 1.2-2.0g / cm 3 .

Citation Information

Patent Citations

  • Production technique of white charcoal

    CN103122252B

  • Novel three-dimensional carbon materials, their preparation methods and applications

    CN108609600B

  • Preparation method of high-yield biomass hard charcoal

    CN116281948A

  • Method for preparing activated carbon from Hunan camellia oleifera shells, activated carbon and application of activated carbon

    CN104803381A

  • Method for quickly preparing activated carbon

    CN106744951A